PET-CT in neuroradiology. Issue 2 (9th August 2019) - Lövblad, Karl-Olof; Bouchez, Laurie; Altrichter, Stephen; Ratib, Osman; Zaidi, Habib; Vargas, Maria Isabel
Positron emission tomography (PET) has a long history in the assessment of brain physiology and pathology; however, its initial use was limited to more academic and scientific settings. This changed radically with the clinical introduction of PET–computed tomography (PET-CT). PET-CT has become an integral part of the radiological armamentarium, especially in the assessment of patients with oncological or cardiovascular disorders. It has until now not found a clear role in neuroradiology. Indeed, magnetic resonance techniques have proven superior for the investigation of brain tumors and inflammatory diseases. However, some newer applications are emerging that can re-center PET-CT clearly in the neuroradiological world such as the investigation of vascular diseases.